Flight path and scheduling effects on perceived jet lag, fatigue, and sleep in footballers traveling to and from national teams - Clements, E.; Ehrmann, F.; Clark, A.; Jones, M.; McCall, A.; Duffield, A. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study examined posttravel perceptual responses of national-team footballers (soccer) following different flight paths, arrival/departure times, and trip contexts.